EXPLORING THE SPEAKING ANXIETY OF ELEMENTARY LEVEL PRIVATE UNIVERSITY STUDENTS OF SOUTH KALIMANTAN AND ATTEMPTS TO SOLVE - M. Arbain; F. Ramadani; H. Novika (Intensive Journal, 2018)
The ultimate goal of language teaching is to enable learners to communicate in the target language they learn. For those who can meet this goal are regarded as high achievers or successful language learners. However, not every language learner can reach this goal. This might be because there are many factors involved in language learning. One of those factors is an anxiety construct in the affective domain, considered as an important affective role in second/foreign language acquisition and could be presumed as ‘a cause of language failure’ (Brown, 2000, p. 141). However, it does not mean students and teacher do nothing. Students are required to find a number of ways to solve or at least reduce their own speaking anxiety. So do the English teacher. They also find a number of strategies to solve or at least reduce the students’ speaking anxiety. This research is intended to describe a number of tactics/tricks carried out by the private university students to reduce their speaking anxiety and the strategies carried out by the lectures to solve their university students. The research design employed was descriptive with interview as the instrument. The research reveals that a number of university students carried out a number of tactics/tricks, which were referred to mental effect relaxation (MER) and physical effects reduction (PER). Meanwhile to reduce their speaking anxiety, the three lectures were reported to carrying out a number of strategies, which were referred to mental-related assistance (MRA) and knowledge-based assistance (KBA).